Volume 8: Microturbines, Turbochargers and Small Turbomachines; Steam Turbines 2016
DOI: 10.1115/gt2016-56360
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Force on Multi-Stage and Multi-Passage Turbine Long Blade Rows Induced by Wet-Steam Flows

Abstract: At the 2015 ASME Turbo Expo in Montreal, we presented a paper on unsteady three-dimensional wet-steam flow simulations for the last three stages of a low-pressure real steam turbine. We then focused on the investigation of unsteady wetness in the three-stage blade passages, which was conducted by assuming the same number of blades in the previous study and the real blade number. The obtained results showed that wetness is definitively influenced by the blade number difference between the stator and the rotor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
1
8
1
Order By: Relevance
“…The condensation coefficient and the empirical parameter α in the Young's modification were specified to 1.0 and 5.0 in this study. The wetness values that we obtained varied slightly from those obtained in our previous study (Miyazawa et al, 2016). stage).…”
Section: Computational Domainscontrasting
confidence: 48%
See 3 more Smart Citations
“…The condensation coefficient and the empirical parameter α in the Young's modification were specified to 1.0 and 5.0 in this study. The wetness values that we obtained varied slightly from those obtained in our previous study (Miyazawa et al, 2016). stage).…”
Section: Computational Domainscontrasting
confidence: 48%
“…We generated 91 × 91 × 181 grid points for each blade passage, 61 × 91 × 181 grid points for each inlet and outlet region, and 31 × 91 × 181 grid points for each intermediate region in the axial, tangential, and radial directions. The grid topology was the same as that used in our previous studies (Miyake et al, 2015) (Miyazawa et al, 2016) and the grid points employed in this study was the same with those in the study (Miyazawa et al, 2016) . Table 2 shows the computational flow conditions.…”
Section: Computational Domainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following such early studies, numerical studies for wet-steam flows have been further reported and 2-D and 3-D wet-steam flow simulations have become possible due to recent improvements in computing power. Our group simulated unsteady wet-steam flows through multi-stage stator and rotor blade rows accounting for nonequilibrium condensation (Miyazawa et al, 2016). As part of the trend of wet-steam flow studies, a Cambridge University group promoted a workshop for wet-steam nozzle flow simulation named the International Wet Steam Modeling Project (IWSMP) to revalidate the condensation models currently used in wet-steam flow simulations.…”
Section: Introductionmentioning
confidence: 99%